AZERBAIJAN: IRANIAN VECTOR OF RELIGIOUS REVIVAL - KULIEV, Elmir (CENTRAL ASIA AND THE CAUCASUS, 2005)
Together with independence, the peoples of Azerbaijan acquired the freedom of worship envisaged in the republic’s constitution, which serves as the legal basis of religious resurrection in the country. The upsurge of religious feelings is partly explained by what a casual observer may take for a paradox. I have in mind the lack of spirituality caused, among other things, by the absence of religious continuity among the younger generation, which is willingly embracing Islam. Islamic religious and philosophical thought in Azerbaijan is struggling through an ideological fog to bring the nation back to its traditional moral and spiritual values. The traditional clergy and religious radicals exploiting the ideological vacuum left by socialism are little interested in the resurging interest in Islam and its potential contribution to the country’s rebirth.In fact, the clergy, which betrayed its inability to meet the current challenges, has become a serious obstacle for those who wanted to reach religious perfection: many of them cannot accept the archaic and even anti-social tradition which imposes ideological limitations and bans free thinking. Those members of the clergy who have retained their former role as Islam’s social-historical sheath allegedly designed to shape the religion’s environment are rejected together with the fossilized traditions. We should admit, however, that it was thanks to the conservative-minded clergy that religious resurrection in Azerbaijan did not acquire political hues. However, this should not be taken to mean that the clergy is not responsible for the deep internal and external crisis of religion in Azerbaijan.Today, the revivalist movement, which has already acquired a fairly wide scope, stands opposed to the traditional religious leaders. It has failed so far to grasp the meaning of the key tasks civil society should address on its road toward democracy. The revivalists passionately desire to cleanse religion of communist impurities; they cherish its spiritual harmony, while their approach to reforming Islamic rituals deserves attention. They have not accumulated enough internal resources so far to use religion to deal with the country’s major social problems.